Improving Mathematical Reasoning Through Geogebra-Assisted Discovery Learning - Redy Williantama Zulhafendi; Yarman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to improve the mathematical reasoning ability of Grade XI students through the implementation of GeoGebra-assisted discovery learning. The research employed a classroom action research design conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The participants were 40 Grade XI students at SMA Negeri 8 Padang, and the learning material focused on geometric transformations. The main research instrument was an essay test developed based on indicators of mathematical reasoning ability. Data were analyzed by examining the average test scores and learning completeness in each cycle. The results showed that the application of GeoGebra-assisted discovery learning successfully improved students’ mathematical reasoning skills. This improvement was indicated by an increase in the average test score from 63.15% in Cycle I to 81.22% in Cycle II. In addition, learning completeness increased from 55% in Cycle I to 80% in Cycle II, thereby meeting the predetermined success indicator of at least 70% of students achieving improvement. Discovery-based learning supported by GeoGebra encouraged students to actively observe patterns, formulate conjectures, examine arguments, and draw conclusions through direct visual exploration. These findings suggest that the integration of technological media into active learning models can foster deeper, more logical, and more structured mathematical reasoning processes. Therefore, GeoGebra-assisted discovery learning is effective in enhancing the mathematical reasoning ability of Grade XI students.